MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS 7 SMP PADA MATERI ARITMATIKA SOSIAL DENGAN MENGGUNAKAN PENDEKATAN PROBLEM BASED-LEARNING - Didah Hamidah; Luvy Sylviana Zanthy; Dwi Ratna Siwi (IKIP Siliwangi, 2023)
This study aims to increase the motivation to learn mathematics in social arithmetic material by using a problem based-learning approach. This type of research is CAR using the CAR model design created by Kemmis and Mc Taggart. The subjects of this study were 10th graders at SMPN 14 Cimahi. The data collection technique used a learning motivation questionnaire with 5 indicators and 10 questions each 5 positive statements and 5 negative statements. The results of this study indicate an increase in student learning motivation in each cycle with good to very good categories. The use of problem based-learning approach is proven to be able to increase students' learning motivation.